Intrava DX for Residual Weed Control in Spring Fallow - Patrick W. Geier; K.B. Jeremie Kouame (Kansas Agricultural Experiment Station Research Reports, 2025)
Intrava DX, KFD-881, and Preview herbicide mixtures provided excellent control of kochia, Palmer amaranth, and Russian thistle through four weeks following application at Garden City and near complete common lambsquarters and horseweed control at Hays. At Garden City, Russian thistle control exceeded 94% with all herbicides at 77 days after treatment (DAT). Kochia control remained excellent with Preview at either rate 77 DAT as well. Only the high rates of Intrava DX and KFD-881 provided as much as 70% Palmer amaranth control at 77 DAT at Garden City. Overall, Palmer amaranth control was higher at Hays, but the high rates of Intrava DX and KFD-881 were most effective at this location as well. These results show promise that these herbicides may effectively control weeds in fallow for extended periods of time.